Medieval liturgical chant and patristic exegesis : words and music in the second-mode tracts - Hornby, Emma, 1973- (Studies in medieval and Renaissance music, 2009)
How do text and melody relate in western liturgical chant? Is the music simply an abstract vehicle for the text, or does it articulate textual structure and meaning? These questions are addressed here through a case study of the second-mode tracts, length.